(untitled) (Journal of Informatics Education and Research, 2026)
The contemporary revival of the Indian Knowledge System (IKS) invites a re‑examination of classical concepts that shaped ethics, governance and social welfare in pre‑modern South Asia. This enhanced research paper draws on themes from traditional Indian knowledge—definitions of śāstra, meanings of artha, the cycle of yogakṣema, the upāyas or strategies of statecraft, detailed typologies of sāma (conciliation) and dāna (charitable giving)—and demonstrates their practical application in contemporary Indian governance and policy-making. This paper reconstructs an integrated framework of Indian thought on prosperity and public order, analyzing how these ancient principles manifest in modern policies such as the National Education Policy (NEP) 2020, the Panchayats (Extension to Scheduled Areas) Act (PESA) 1996, and various tribal development initiatives. The research incorporates primary data from government reports, secondary data from academic sources, and extensive citations to demonstrate the living relevance of IKS in 21st-century India.